Investigation of the Salt Chuck copper mine, Kasaan Peninsula, Prince of Wales Island, southeastern Alaska - Fosse, E.L.; Tolonen, A.W.; Thorne, R.L.; Shepard, J.G.; Holt, S. P. ([Washington, D.C.] : U.S. Dept. of the Interior, Bureau of Mines, 1948)
"October 1948." Mode of access: Internet.